Evaluation of haemoglobin in blister fluid as an indicator of paediatric burn wound depth. Issue 5 (August 2015) - Tanzer, Catherine; Sampson, Dayle L.; Broadbent, James A.; Cuttle, Leila; Kempf, Margit; Kimble, Roy M.; Upton, Zee; Parker, Tony J.
Highlights: We measured free haemoglobin abundance in paediatric burn blister fluid. Haemoglobin was associated with burn depth and time from injury to presentation. Haemoglobin abundance was also related to time to reepithelialisation. The consequences of free haemoglobin in burn wound environments remains unclear. Abstract: The early and accurate assessment of burns is essential to inform patient treatment regimens; however, this first critical step in clinical practice remains a challenge for specialist burns clinicians worldwide. In this regard, protein biomarkers are a potential adjunct diagnostic tool to assist experienced clinical judgement. Free circulating haemoglobin has previously shown some promise as an indicator of burn depth in a murine animal model. Using blister fluid collected from paediatric burn patients, haemoglobin abundance was measured using semi-quantitative Western blot and immunoassays. Although a trend was observed in which haemoglobin abundance increased with burn wound severity, several patient samples deviated significantly from this trend. Further, it was found that haemoglobin concentration decreased significantly when whole cells, cell debris and fibrinous matrix was removed from the blister fluid by centrifugation; although the relationship to depth was still present. Statistical analyses showed that haemoglobin abundance in the fluid was more strongly related to the time between injury and sample collection and the time taken for spontaneous re-epithelialisation. We hypothesise that prolonged exposure to the blister fluid microenvironment may result in an increased haemoglobin abundance due to erythrocyte lysis, and delayed wound healing.